PRODUK DOMESTIK REGIONAL BRUTO DAN JUMLAH PENGANGGURAN TERHADAP GARIS KEMISKINAN DI KABUPATEN MUARO JAMBI - Putri, Osi Hayuni (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2022)
This study uses a type of causality research that belongs to the quantity approach. This study uses secondary data, and uses the independent variable, namely GRDP (X1), Total Unemployment (X2) and the dependent variable, namely the Poverty Line (Y) in Muaro Jambi Regency for 10 years starting from 2011-2020. The time used in this research is 3 months (July-September) 2021. From the results of the analysis and discussion, it can be concluded as follows: 1. Simultaneously the PDRB and the number of unemployed have a significant effect on the poverty line in Muaro Jambi Regency in 2011 -2020 with F count > F table. Partially, GRDP does not significant effect on the poverty line in Muaro Jambi Regency in 2011-2020 because the value of T-count < T-table. While the number of unemployed partially has a significantly affect the poverty line in Muaro Jambi Regency in 2011-2020 because the value of T-count > T-table. 2. The magnitude of the simultaneous influence between the variables of GRDP and the number of unemployed on the poverty line in Muaro Jambi Regency in 2011-2020 is 87.8% while the remaining 12.2% is influenced by other factors not examined in this study. While partially the influence of the GRDP on the poverty line in Muaro Jambi Regency in 2011-2020 is 83.496% and the magnitude of the influence of the variable number of unemployed on the poverty line in Muaro Jambi Regency in 2011-2020 is 4.299%.